2016
DOI: 10.1016/j.ssresearch.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Universalism, conservation and attitudes toward minority groups

Abstract: Findings from previous studies corroborate the hypothesis that universalism and conservation values are associated with negative attitudes toward immigration. In the current study we examine whether universalism and conservation values also play a critical role in the explanation of attitudes toward other minority groups. Drawing on previous research on group-focused enmity, we explore its relations with universalism and conservation values in a German sample. Employing structural equation modeling, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
4
36
0
6
Order By: Relevance
“…Indeed, the motivations underlying conformity and tradition and universalism values are highly associated with cultural elements and are thus likely to be particularly related to symbolic threat. 3 Therefore, and in line with previous studies on the issue (Beierlein, Kuntz, and Davidov 2016;Davidov and Meuleman 2012;Schwarz 2008b, Davidov et al 2014;Sagiv and Schwartz 1995), we arrive at the following hypotheses:…”
Section: Universalism Conformity Tradition and Opposition To Immigsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, the motivations underlying conformity and tradition and universalism values are highly associated with cultural elements and are thus likely to be particularly related to symbolic threat. 3 Therefore, and in line with previous studies on the issue (Beierlein, Kuntz, and Davidov 2016;Davidov and Meuleman 2012;Schwarz 2008b, Davidov et al 2014;Sagiv and Schwartz 1995), we arrive at the following hypotheses:…”
Section: Universalism Conformity Tradition and Opposition To Immigsupporting
confidence: 84%
“…Notwithstanding the importance of the structural explanations, socio-demographic characteristics of individuals, and their political ideology, several studies noted that individual human values have a paramount importance for the explanation of negative sentiments towards immigrants (Beierlein, Kuntz, and Davidov 2016;Davidov and Meuleman 2012;Davidov et al 2008aDavidov et al , 2014Sagiv and Schwartz 1995;Schwartz 2006aSchwartz , 2007. These researchers demonstrated that basic human values are associated with attitudes towards minorities in general and immigrants in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have identified value priorities as crucial factors shaping individuals' attitudes towards ethnic minorities and immigrants (Beierlein, Kuntz, and Davidov 2016;Davidov et al 2008;Sagiv and Schwartz 1995). According to Schwartz' (1992) theory, basic human values are 'desirable transsituational goals, varying in importance, that serve as guiding principles in the life of a person or other social entity' (Schwartz 1994, 21).…”
Section: Related Theoretical Framework: Intergroup Contact Theory (Imentioning
confidence: 99%
“…Values whose expression or attainment are promoted or blocked by the presence of minorities in a country are likely to affect perceptions of ethnic threat (Sagiv and Schwartz 1995). Previous research has shown that this mechanism is particularly relevant for two value types, namely universalism (i.e., the motivation to appreciate differences among individuals, as well as understand, tolerate and protect the welfare of all people) and conformity-tradition (i.e., the motivation to maintain the beliefs, customs and practices of one's culture and family and to avoid violation of conventional expectations and norms) (Beierlein et al 2016;Davidov and Meuleman 2012;Davidov et al 2014). The presence of different ethnic groups offers opportunities to realise universalism values, and at the same time challenges conformitytradition values.…”
Section: Related Theoretical Framework: Intergroup Contact Theory (Imentioning
confidence: 99%
“…Empirical evidence has confirmed the role values play in shaping people’s response to immigration. Negative feelings toward outgroups in general and immigrants in particular are typical of people who endorse conservation (especially security, but also conformity; Beierlein, Kuntz, & Davidov, ; Davidov et al, ; Vecchione et al, ; Wolf et al, ), but also of those who ascribe low importance to the values of self‐transcendence (especially universalism; Beierlein et al, ; Davidov et al, ; Leong & Ward, ; Sagiv & Schwartz, ; Saroglou & Galand, ; Schwartz, ; Vecchione et al, ; Wolf et al, ), and who show strong desire for power (Vecchione et al, ). These effects were replicated across European countries (Davidov et al, ; Vecchione et al, ).…”
Section: Individual‐level Predictors: Human Values Sdo and Rwamentioning
confidence: 99%